Implikasi Aliran Esensialisme dalam Budaya Pendidikan Indonesia di Sekolah Dasar - Nadhyva Maulida Farih; Dya A’yun (Jurnal Kajian dan Penelitian Umum, 2024)
Essentialism describes schools as the main agent of student character building by emphasizing local cultural values, such as honesty, discipline, responsibility, and mutual respect. The purpose of this study is to find out the implications of essentialism in emphasizing local cultural values, the importance of basic knowledge, and character education that have a positive impact on student development in facing the challenges of everyday life. The method of data collection used is by collecting literature studies in the form of books, journals and interviewing teachers of SDN Patengteng 1. The results of the study of essentialism in education encourage the integration of cultural values, basic knowledge includes subjects such as math, science, language and history. The essentialism approach has a primary focus on student character building. Through this approach, students can develop positive attitudes and good behavior in daily life while understanding and appreciating the cultural diversity around them.